Analisis Citra Satelit Himawari-8 Terkait Kejadian Puting Beliung Di Kabupaten Bogor (Studi Kasus 02 November 2021) - Ade Febrian; Syaiful Amri (Universitas Islam Negeri Alauddin Makassar, 2023)
Puting Beliung is a strong-rotating wind originating from Cumulonimbus clouds with a speed of more than 34.8 knots or 64.4 km/hour that occurs short time. Puting Beliung occurred on November 2, 2021, at 2 pm in the Kampung Dukuh area, Pasirmukti Village, Citeureup District, Bogor Regency (106° 53' 47.99